Characterization in silico of bioactive compound in tea plant as a potentials inhibitor of SARS-CoV-2 Mpro - Mohamad Endy Yulianto, Ari Yuniastuti, Dadan Rohdiana, Vita Paramita, Hermawan Dwi Ariyanto, Rizka Amalia, Sutrisno Sutrisno, Indah Hartati, Shabri Shabri, Retno Dwi Nyamiati, Siti Rahmawati (Journal of Applied Pharmaceutical Science, 2022)
One of the screenings of the chemical structure that has the potential as an active major protease (Mpro) inhibitor in SARS-CoV-2 is bioactive compounds, such as oolonghomobisflavan-A, theaflavin-3-O-gallate, and theaflavin (TF). These bioactive compounds are main components of catechin oxidation, which contribute color, taste, and aroma to black tea. Enzymatic oxidation events in black tea processing have started at the beginning of the mill. In silico studies of active site Mpro as an inhibitor of SARS-CoV-2 were conducted using Protein Data Bank from a web platform. This analysis was carried out using the AutoDock Vina software integrated with PyRx 0.8. The molecular docking results were visualized in 3D and 2D with the BIOVIA Discovery Studio software with the result that amino acid residues and chemical bonds formed were visible, indicating the binding site of a target protein. The production of bioactive compounds through the tea fermentation process accelerated the oxidation rate of catechins into the contained bioactive compounds, which was analyzed using a spectrophotometer with a wavelength of 380 nm. Bioactive compound analysis used the response surface methodology. The results of docking the oolonghomobisflavan compound with Mpro indicated the highest binding affinity, namely −8.0 kcal/mol; however, the oolonghomobisflavan compound with Mpro did not show the same interaction as the control. On the contrary, for the docking of theaflavin-3’-Ogallate with Mpro, the binding affinity was −6.3 kcal/mol and showed the same interaction with the control, namely, LysA:137, where the compound formed hydrogen bonds, and analysis of the selected compound was carried out on the theaflavin-3’-O-gallate compound. The optimal operating conditions for the extraction process were at a flow rate of 17.65 l/minute with a fermentation time of 50 minutes, which produced a maximum theaflavin level of 0.938%.
Keywords: Tea, bioactive compound, theaflavin, SARS-CoV-2